TABU BAHASA WANITA TENTANG ISU CHILDFREE PADA AKUN INSTAGRAM @GITASAV - Yunita, Tria; Widyastuti, Chattri Sigit (Universitas Hamzanwadi, 2024)
This research discusses language taboos. Language taboo is defined as speech that is prohibited or refers to taboos in action, social or cultural. This research aims to examine the types of women's taboo language on the Instagram account @gitasav which raises the issue of childfree. This research uses the theory of types of language taboo from Timothy Jay which divides language taboo into 7 types. In this research, the focus is on the types of vulgar language taboos and insulting language taboos. The method of providing data used is the observation method using note-taking techniques. The data analysis method used is the matching method and the technique of asking comparisons (HBS) and comparing the main points (HBSP). The results of this research show that the use of taboo language, insults, is more dominant in the comments column of the @gitasav account as a form of disapproval of the childfree issue. In this research, 9 data on women's language taboos were found which were categorized into 3 data types of vulgar language and 6 data types of insults.